(untitled) (American Journal of Islam and Society, 2011)
Timothy Daniels’ Islamic Spectrum in Java critically examines the myriad of ways in which Javanese Muslims draw on religious and secular ideas to project desirable futures for their local societies, for the Indonesian nation, and for Indonesia’s place in the global economic, political, and cultural structures of the twenty-first century. This book identifies a broad range of desirable futures projected by Javanese Muslims, as well as a range of beliefs and practices that comprise Javanese Islam (12). While this engaging work is very likely to appeal to scholars in many fields, theoretically and methodologically it is foremost an anthropological study. Synthesizing symbolic and cognitive anthropology in order to “provide ‘thick description’ 1 symbols . . . and to ascertain the social distribution of knowledge and formation of mental representations in various contexts (4).” Daniels draws primarily on ethnographic fieldwork conducted in the Yogyakarta area of south-central Java from 2003 to 2004 ...